2013
DOI: 10.2459/jcm.0b013e32834eacf0
|View full text |Cite
|
Sign up to set email alerts
|

Relation between right and left ventricular function in patients undergoing chronic dialysis

Abstract: AVF-induced RVD may contribute to LVD in dialysis patients. AVF plays a pivotal role in triggering LVD via right-to-left ventricular interdependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…ESRD, end-stage renal disease; AVF, arteriovenous fistula; RV, right ventricular; LV, left ventricular; ILVM, inappropriate left ventricular mass. line with these studies, we reported for the first time that right-to-left ventricular interdependence represents a putative mechanism underlying LV dysfunction in patients undergoing chronic dialysis [10]. Particularly, AVF seems to be critically involved in this phenomenon (Fig.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…ESRD, end-stage renal disease; AVF, arteriovenous fistula; RV, right ventricular; LV, left ventricular; ILVM, inappropriate left ventricular mass. line with these studies, we reported for the first time that right-to-left ventricular interdependence represents a putative mechanism underlying LV dysfunction in patients undergoing chronic dialysis [10]. Particularly, AVF seems to be critically involved in this phenomenon (Fig.…”
supporting
confidence: 72%
“…1). In a further study we investigated the role of AVF-induced RV dysfunction as a putative determinant of LV dysfunction in dialysis patients without overt cardiovascular disease [10]. Interestingly, myocardial performance index (MPI) of the right ventricle inversely correlated with both conventional and TDI indices of LV systolic and diastolic function and was independently associated with reduced LV ejection fraction.…”
mentioning
confidence: 96%
“…RV systolic dysfunction was independently associated with poor survival even when modeled with age, gender, diabetes, ESRD cause, and AV fistula access in a multivariable analysis. RV dysfunction in HD patients is thought to result from chronic volume overload and is exacerbated by AV fistula access, especially in the brachial position (27,28). RV dysfunction in turn leads to an impaired LV.…”
Section: Discussionmentioning
confidence: 99%
“…RV dysfunction is prevalent among patients with ESRD receiving hemodialysis (25). RV overload and dysfunction may contribute to LV dysfunction through interventricular dependence (26). The current study in this issue of CJASN is the first to report on the beneficial effect of frequent daily hemodialysis on RV end-diastolic volume (RVEDV) and, to a lesser extent, on RV end-systolic volume.…”
mentioning
confidence: 77%